Microglia Inhibition Delays Retinal Degeneration Due to MerTK Phagocytosis Receptor Deficiency - Lew, Deborah S.; Mazzoni, Francesca; Finnemann, Silvia C. (Frontiers in Immunology, 2020)
Retinitis Pigmentosa (RP) is a group of inherited retinal diseases characterized by progressive loss of rod followed by cone photoreceptors. An especially early onset form of RP with blindness in teenage years is caused by mutations in mertk, the gene encoding the clearance phagocytosis receptor Mer tyrosine kinase (MerTK). The cause for blindness in mutant MerTK-associated RP (mutMerTK-RP) is the failure of retinal pigment epithelial cells in diurnal phagocytosis of spent photoreceptor outer segment debris. However, the early onset and very fast progression of degeneration in mutMerTK-RP remains unexplained. Here, we explored the role of microglia in the Royal College of Surgeons (RCS) rat model of mutMerTK-RP. We found elevated levels of inflammatory cytokines and CD68 microglia activation marker, and more ionized calcium-binding adapter molecule 1 (Iba-1) positive microglia in RCS retina when compared to wild-type retina as early as postnatal day 14 (P14). Strikingly, renewal of photoreceptor outer segments in P14 wild-type rat retina is still immature with low levels of RPE phagocytosis implying that at this early age lack of this process in RCS rats is unlikely to distress photoreceptors. Although the total number of Iba-1 positive retinal microglia remains constant from P14 to P30, we observed increasing numbers of microglia in the outer retina from P20 implying migration to the outer retina before onset of photoreceptor cell death at ~P25. Iba-1 and CD68 levels also increase in the retina during this time period suggesting microglia activation. To determine whether microglia affect the degenerative process, we suppressed retinal microglia in vivo using tamoxifen or a combination of tamoxifen and liposomal clodronate. Treatments partly prevented elevation of Iba-1 and CD68 and relocalization of microglia. Moreover, treatments led to partial but significant retention of photoreceptor viability and photoreceptor function. We conclude that loss of the phagocytosis receptor MerTK causes microglia activation and relocalization in the retina before lack of RPE phagocytosis causes overt retinal degeneration, and that microglia activities accelerate loss of photoreceptors in mutMerTK-RP. These results suggest that therapies targeting microglia may delay onset and slow the progression of this blinding disease.